Covid-19 and Older Adults: The Paradox of Control Measures - Iwuagwu, Anthony Obinna; Ngwu, Christopher Ndubuisi (Advances in Social Sciences Research Journal, 2021)
It is no longer news that Covid-19 pandemic has become a major public health issue around the world and affected day to day activities of public life. Medical experts around the world were overwhelmed by the Covid-19 virus outbreak and for a long time were unable to provide a vaccine or any pharmaceutical treatment. Countries were therefore forced to adopt unprecedented Infection Prevention and Control (IPC) measures to mitigate the spread and impact of the virus. These measures which are non-pharmacological includes, social distancing, social isolation, lockdown, constant washing of hands, wearing of face mask and protective gloves etc. However, these measures aimed at protecting the health care systems, have had some side effects on the health and well-being of older adults. In this letter, we have highlighted social distancing as the main challenge and a paradox for older peoples wellbeing during the Covid-19 pandemic outbreak. The merits of the IPC measures notwithstanding, its long and short term consequences for the mental health of older adults calls for concern. Among other recommendations, professionals of ageing and geriatrics are recommended to help set a balance in IPC measures and mental health of older people in this Covid-19 era.